Opportunities for prevention and intervention with young children: lessons from the Canadian incidence study of reported child abuse and neglect - Fallon Barbara; Ma Jennifer; Allan Kate; Pillhofer Melanie; Trocmé Nico; Jud Andreas (BMC, 2013)
Abstract Background The most effective way to provide support to caregivers with infants in order to promote good health, social, emotional and developmental outcomes is the subject of numerous debates in the literature. In Canada, each province adopts a different approach which range from universal to targeted programs. Nonetheless, each year a group of vulnerable infants is identified to the child welfare system with concerns about their well-being and safety. This study examines maltreatment-related investigations in Canada involving children under the age of one year to identify which factors determine service provision at the conclusion of the investigation. Methods A secondary analysis of the Canadian Incidence Study of Reported Child Abuse and Neglect CIS-2008 (PHAC, 2010) dataset was conducted. Multivariate analyses were conducted to understand the profile of investigations involving infants (n=1,203) and which predictors were significant in the decision to transfer a case to ongoing services at the conclusion of the investigation. Logistic Regression and Classification and Regression Trees (CART) were conducted to examine the relationship between the outcome and predictors. Results The results suggest that there are three main sources that refer infants to the Canadian child welfare system: hospital, police, and non-professionals. Infant maltreatment-related investigations involve young caregivers who struggle with poverty, single-parenthood, drug/solvent and alcohol abuse, mental health issues, lack of social supports, and intimate partner violence. Across the three referral sources, primary caregiver risk factors are the strongest predictor of the decision to transfer a case to ongoing services. Conclusions Multivariate analyses indicate that the presence of infant concerns does not predict ongoing service provision, except when the infant is identified with positive toxicology at birth. The opportunity for early intervention and the need to tailor interventions for specific caregiver risk factors is discussed.